2018
DOI: 10.1038/s41598-018-28511-w
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 mutant zebrafish have an enhanced interferon gamma response and improved survival against a Mycobacterium marinum infection

Abstract: Tuberculosis ranks as one of the world’s deadliest infectious diseases causing more than a million casualties annually. IL10 inhibits the function of Th1 type cells, and IL10 deficiency has been associated with an improved resistance against Mycobacterium tuberculosis infection in a mouse model. Here, we utilized M. marinum infection in the zebrafish (Danio rerio) as a model for studying Il10 in the host response against mycobacteria. Unchallenged, nonsense il10e46/e46 mutant zebrafish were fertile and phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 85 publications
(125 reference statements)
1
23
0
Order By: Relevance
“…Th1 (interferon-gamma) also suppresses specific antigen response by blocking the inflammatory response induced by cytokines such as inter-leukine-10 (IL-10) [37]. It seems that by suppressing IFN-γ production, the suppression of this cytokine on TH17 cells also diminishes, resulting in an increase in IL17 production [16].As shown by Fig. 5, the highest expression of interferon gamma gene was observed in the control and glucose-containing control groups (G-CTRL, G + CTRL) (p < 0.05).…”
Section: Gene Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Th1 (interferon-gamma) also suppresses specific antigen response by blocking the inflammatory response induced by cytokines such as inter-leukine-10 (IL-10) [37]. It seems that by suppressing IFN-γ production, the suppression of this cytokine on TH17 cells also diminishes, resulting in an increase in IL17 production [16].As shown by Fig. 5, the highest expression of interferon gamma gene was observed in the control and glucose-containing control groups (G-CTRL, G + CTRL) (p < 0.05).…”
Section: Gene Factorsmentioning
confidence: 99%
“…This study indicated that beta-cell number could be significantly increased using metformin [14].Inflammatory biomarker genes are found in diabetic and obese individuals, and these biomarkers can predict the progression of type 2 diabetes. In the present study, we investigate the possibility of tracking the inflammation in diabetes type 2 induced model of Zebrafish in the intestine and expression of TNF-α [15], IFN-γ [16] and IL-1β genes [17] by chemical (metformin) and herbal (Silymarin) alone and as combined drugs. Indeed, we intend to introduce a novel herbal and chemical combination compound to reduce the effects the possible inflammation caused by hyperglycemia due to high concentration of glucose uptake in zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…No significant morphological changes were observed in the gills of il4/13a −/− , il4/13b −/− or il4/13a;b −/− fish compared to wildtype (Figure 4A), suggesting that loss of functional IL-4/13A and IL-4/13B does not affect tissue morphology despite a shift toward type 1 immunity. For comparison, we examined the gills of il10 e46/e46 mutants lacking functional IL-10, which have also been reported to shift towards type 1 immune responses (38). A thickening of the gill arch and filaments, as well as lamellar epithelial changes were detected in the absence of functional IL-10, indicating a role for this cytokine in maintaining gill homeostasis in adult zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…An anti-inflammatory role for IL-10 has been previously shown in carp (64) and in zebrafish gut (65). Moreover, suppression of Th1 cell response and cytokine production was reported in a zebrafish M.marinum model (38). For the first time to our knowledge, we addressed the function of zebrafish IL-10 in the gills and demonstrated its importance in preventing inflammation in this mucosal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…M. marinum induced expression of IL-10 has been observed in goldfish primary kidney monocytes and macrophages (Grayfer et al, 2011), although no apparent increases of IL-10 were observed in spleen or kidney tissues during infections (Hodgkinson et al, 2012), and introduction of recombinant IL-10 did not alter the viability of M. marinum within goldfish phagocytes (Hodgkinson et al, 2012). In zebrafish, IL-10 mutants showed enhanced survival and enhanced interferon gamma response following chronic M. marinum infection (Harjula et al, 2018).…”
Section: Il-10mentioning
confidence: 99%